Juridical Analysis of the Crime of Child Trafficking through Illegal Adoption Schemes - Virda Aleyda Rahma; Muhammad Gary Gagarin; Muhamad Abas (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
This study aims to analyze the considerations employed by the Panel of Judges in Decision Number 30/Pid.Sus/2023/PN.Cbi and to examine the obstacles encountered in combating the crime of child trafficking through illegal adoption schemes. The research employs a normative juridical method using statutory, case, and conceptual approaches. The findings indicate that the judges’ legal considerations were consistent with the provisions of Article 83 in conjunction with Article 76F of Law Number 35 of 2014 concerning Child Protection, as they were based on the fulfillment of the elements of the criminal offense and supported by valid evidence. The judges also took into account philosophical and sociological considerations in determining the sentence. However, the sentence imposed on the defendant, namely four (4) years of imprisonment and a fine of IDR 100,000,000, was considered relatively lenient because it was lower than the sentence sought by the Public Prosecutor, namely five (5) years of imprisonment. Consequently, the punishment imposed has not fully reflected substantive justice for the victim. Furthermore, efforts to combat this form of crime continue to face various challenges, including ambiguities in legal norms, weak supervision of child adoption practices, low levels of public legal awareness, and the use of social media as a medium for digitally facilitated criminal activities. Protection for victims also remains suboptimal, particularly with regard to psychological recovery, rehabilitation, and restitution.